2011
DOI: 10.1084/jem.20101920
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin deficiency is associated with reduced neutrophil recruitment but increased vascular permeability in vivo

Abstract: Cortactin is required for endothelial barrier function and leukocyte recruitment in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 83 publications
(114 reference statements)
9
111
0
Order By: Relevance
“…siRNA-mediated knockdown of cortactin in fibroblasts (85), smooth muscle cells (86), tumor cells (51,(87)(88)(89)(90), or OCs (52, 53) prevents the formation of podosome and invadopodia. To determine which role cortactin plays in podosome patterning and belt formation, we used OCs derived from cortactin knockout mice (36). In contrast to previous reports, we found that cortactin is dispensable for podosome formation in OCs.…”
Section: Discussionmentioning
confidence: 76%
“…siRNA-mediated knockdown of cortactin in fibroblasts (85), smooth muscle cells (86), tumor cells (51,(87)(88)(89)(90), or OCs (52, 53) prevents the formation of podosome and invadopodia. To determine which role cortactin plays in podosome patterning and belt formation, we used OCs derived from cortactin knockout mice (36). In contrast to previous reports, we found that cortactin is dispensable for podosome formation in OCs.…”
Section: Discussionmentioning
confidence: 76%
“…Transendothelial migration of isolated murine neutrophils though a bEnd.5 endothelial cell monolayer was analyzed as described before (58).…”
Section: Methodsmentioning
confidence: 99%
“…[68][69][70][71][72][73][74][75][76] Importantly, recent data indicates the involvement of p120 ctn in controlling ARP2/3 complex-mediated actin polymerization at endothelial junctions, by binding to the nuclear-promoting factors Wiskott-Aldrich Syndrome Protein (N-WASP) 21 and to cortactin. 77,78 Both the ARP2/3 complex 11,21 and cortactin [79][80][81][82][83][84][85] control endothelial integrity, and particularly, N-WASP control ARP2/3 complex-mediated formation of new VE-cadherin adhesion sites, which drive the VE-cadherin dynamics.…”
Section: Impact Of α-Catenin In Linking Actin Filaments To the Ve-cadmentioning
confidence: 99%
“…Another protein that controls the ARP2/3 complex activity is cortactin, a class II NPF that has been demonstrated to control endothelial barrier function and leucocyte transmigration. 79,80,83,85,99,100 Furthermore, cortactin has multiple functions in cell motility and is able to activate N-WASP. 101 For further readings to cortactin, please see recent reviews.…”
Section: The Arp2/3 Complex a Central Player In Junction Dynamics Ofmentioning
confidence: 99%
See 1 more Smart Citation